Questioning the link between organizational justice and external procedural justice in police–citizen interactions - Borchardt, David J (International journal of police science & management, 2024)
External procedural justice in police–citizen interactions has been found to have a relationship with cooperation, compliance, and police legitimacy. The individual dimensions of organizational justice comprised of distributive, procedural, interpersonal, and informational justice, have been less frequently examined. Organizational justice has been found to be associated with many desirable outcomes both within policing and in other professions. This study utilized a convenience sample (n = 106) of police officers from five school district police departments in the Houston, Texas metropolitan area. The study combined two sections of two existing instruments for the purpose of examining the extent to which officer perceptions of the four dimensions of organizational justice contribute to officer perceptions of external procedural justice in police–citizen interactions. Results indicated officers rated themselves very highly on the levels of external procedural justice they demonstrated with the public. Officers rated their supervisors highest in the interpersonal justice dimension of organizational justice. Surprisingly, no significant associations emerged between any of the four dimensions of organizational justice and external procedural justice. The findings of this study were inconsistent with the majority of extant research which found that organizational justice correlates with and predicts external procedural justice. This study indicated that officers may overestimate their own utilization of external procedural justice. In addition, it suggests the four dimensions of organizational justice may not predict external procedural justice and raises questions regarding the relationship between these two variables.